Стан підросту і підліску штучного протиерозійного насадження байраку «Військовий» (Північний Степ України) - Бессонова, Валентина Петрівна; Bessonova, Valentina; Пономарьова, Олена Анатоліївна; Ponomariova, Olena (Запорізький національний університет, 2017)
Досліджували формування підросту та підліску у штучному насадженні робінії звичайної на схилі північної експозиції байраку. Найменша щільність як підросту, так і підліску виявлена у верхній частині схилу. Найбільша кількість підросту сформувалася у середній частині схилу, чисельність підліску найбільша в тальвегу. Підріст представлений 7-ма видами, максимальна кількість видів підліску на пробних ділянках – 11. Найбільшу частку від загального числа екземплярів підросту становить груша звичайна. Підріст робінії звичайної в однопородному насадженні майже відсутній, що з часом без відповідних лісівничих заходів може призвести до сукцесійних змін насадження. У підліску переважають глід одноматочковий і клен гостролистий.The species composition and qualitative state of undergrowth and underbrush in the artificial anti-erosion plantation of robinium of ordinary (10Рз) in different forest-tree conditions were determined. Formation of the undergrowth and the underbrush was analyzed on three test sites. The first is located in a talvage, and a stream flows through its bottom. The second area is in the middle third of the slope of the northern exposition, and the third is in its upper third. On experimental sites marked by different composition, age and growth status. The number of undergrowth in talvege is 720 pieces / ha, inside the slope is 1330 pieces / ha, on the upper part – 470 pieces / ha. Undergrowth is represented by plants belonging to 7 species at all trial sites. In the thalweg and the upper part of the slope, the largest share is the undergrowth of pears. In the middle of the slope prevail oak and pear. Robinia pseudoacacia takes the third place. The highest number in the upper part and in talvage is the average undergrowth. In the middle part of the ravine the number of middle and large undergrowth is almost the same. The smallest number is of small undergrowth in all trial areas. The large undergrowth is represented mainly by fruit trees: apple, pear, apricot. A lot of the average undergrowth has the mulberry, plum, apricot and pear. The small undergrowth is inherent in oak, robinia. Underbrush’s are represented by 12 kinds. The most species are in thalweg – 11 species, the least in the middle part of the slope – 7. The most common are hawthorn and maple. The lowest density of undergrowth and underbrush was found on the upper third of the slope. This is due to small afforestation, a rare arrangement of trees, soil retention by steppe grasses, a large anthropogenic load. The index of the life state of the undergrowth and underbrush on the trial plots studied is assessed as healthy.
Тhe state of undergrowth of the artificial anti-erosion plantation of the "viysykova" bairak (northern steppe of Ukraine)
Keywords: штучне насадження; аrtificial planting; підгін; vitality conditions; підлісок; underbrush; життєвий стан; life camp